Microfluidic Free‐Flow Paper Electrochromatography for Continuous Separation of Glycans. Issue 9 (2nd May 2022) - Liu, Yingchao; Huang, Yuanyu; Wu, Mengxi; Kong, Siyuan; Cao, Weiqian; Li, Shunxiang; Yan, Guoquan; Liu, Baohong; Yang, Pengyuan; Zhang, Quanqing; Qiao, Liang; Shen, Huali
Abstract: Microfluidic free‐flow electrophoresis (μ‐FFE) is widely used for continuous separation of charged analytes. However, μ‐FFE is limited in the separation of analytes with the same electrophoretic mobility. In this work, we developed a novel microfluidic free‐flow paper electrochromatography (μ‐FFPE) by combining μ‐FFE with filter paper‐based chromatography, enabling continuous separation of analytes through the mechanism of both μ‐FFE and paper chromatography. Numerical simulation was applied to demonstrate the advantages of adding filter paper as the stationary phase of μ‐FFE. With the filter paper, a more stable separation system was achieved. The device was applied to the separation of simple mixtures of dyes and complex mixtures of glycans. With the μ‐FFPE fractionation, much more glycans and glycan types can be identified by LC‐MS, demonstrating the value of the method in biological analysis. The μ‐FFPE can provide a new platform for the separation and analysis of various biological molecules. Abstract : Flowing freely : A novel microfluidic free‐flow paper electrochromatography (μ‐FFPE) device is developed which combines microfluidic free‐flow electrophoresis (μ‐FFE) and filter paper‐based chromatography, enabling the continuous two‐dimensional separation of complex analytes. The μ‐FFPE shows good analytical performance for the fractionation of glycans and can provide a new platform for the separation of various biological molecules.